Peran Kode Etik Profesi Penyelenggara Profesi Hukum - Achmad Asfi Burhanudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
This research was conducted as an effort to analyze the values contained in the legal profession code of ethics. The issues that will be answered in this research are: First, what and how are the basic values contained in the code of ethics for the Indonesian legal profession. Second, what is the role of the legal profession code of ethics. The purpose of this study is to provide an explanation, analysis and assessment of the legal profession code of ethics. The results of this research are expected to provide input for practitioners and policy makers for the enforcement of the legal profession code of ethics. According to the type, this research includes library research because it makes library materials as study material. With qualitative analysis with inductive and deductive thinking methods, this research gets several conclusions. First, the code of ethics for the legal profession in principle contains moral values that underlie a professional personality, namely freedom, justice and honesty. The two codes of ethics for the legal and legal professions are a unity which inherently contains the values of religious teachings so that basically the code of ethics for the legal profession is in line with the values of religious teachings which have a role as a compass pointing the moral direction for the legal profession administrators as well as ensuring the moral quality of the legal profession in society the code of ethics contains values and norms as benchmarks for legal professionals in upholding the authority of the law that is humane and just.